Fungsi pelindung tiroid dan persepsi dokter gigi terhadap penggunaannya pada teknik radiografi sefalometri dan CBCT - Muhammad Yusuf Lubis; Ryna Dwi Yanuaryska; Rini Widyaningrum (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: The aims of this review is to describe thyroid shield function and to look the dentists’ perceptions considering the application in dental radiographic examination, particularly in cephalometric and Cone Beam Computed Tomography (CBCT) examination. Literature Review: The utilization of thyroid shield has been signified reduction of radiation dose about 34% in cephalometric examination and 18-40.1% in CBCT. The absence of universal guidelines has led to minimal perception of dentists on the importance of using thyroid shield as indicated by the low utilization of thyroid shield among patients. This low perception can be improved through adequate education and applied training in the use of thyroid shield. Conclusion: Dentists’ perceptions regarding the application of thyroid shield need to be improved so that the application of thyroid shield can be increased in order to protect patients from the risk of dental radiation exposure.